Pengaruh Shopping Lifestyle, Hedonic Shopping Value, dan E-Wallet terhadap Impulsive Buying: Studi Kasus pada Mahasiswa Manajemen UKI Toraja Angkatan 2022 - Silviages Logo; Olivia Devi Yulian Pompeng; Abedneigo.C. Rambulangi (Universitas Kristen Indonesia Toraja, 2025)
This study aims to examine the influence of shopping lifestyle, hedonic shopping value, and e-wallet on impulsive buying behavior among students of the Management Study Program at the Faculty of Economics, Universitas Kristen Indonesia Toraja. This research is quantitative in nature, using multiple linear regression analysis. The sample consisted of 80 respondents, determined using Slovin's formula and purposive sampling technique as the basis for selecting respondents deemed relevant to the research objectives. The results of the study indicate that, partially, shopping lifestyle significantly influences impulsive buying with a t-value of 3.608 and sig = 0.001, hedonic shopping value significantly influences impulsive buying with a t-value of 2.186 and sig = 0.032, and e-wallet significantly influences impulsive buying with a t-value of 3.043 and sig = 0.003. Simultaneously, all three independent variables significantly affect impulsive buying, with a significance value of 0.000 < 0.05. The coefficient of determination (R2) value of 0.223 indicates that the three independent variables explain 22.3% of the variation in impulsive buying behavior, while the remaining 77.7% is explained by other factors not investigated in this study. These findings suggest that shopping lifestyle, the value gained from shopping, and the convenience of digital transactions through e-wallets are triggers for unplanned buying behavior.